2021
DOI: 10.1002/ldr.3935
|View full text |Cite
|
Sign up to set email alerts
|

Divergent responses of the soil bacteria community to multi‐level nitrogen enrichment in temperate grasslands under different degrees of degradation

Abstract: Nitrogen (N) enrichment has been reported to affect the soil bacteria community in natural temperate grasslands. However, it remains unknown how the bacteria community responds to N enrichment in degraded grasslands. Here, we established multi-level N enrichment experiments in temperate grasslands under non-degraded (ND), moderately degraded (MD), severely degraded (SD), and extremely degraded (ED) sites in northern China. The bacteria community was investigated by highthroughput sequencing and linked to major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
(85 reference statements)
0
12
0
Order By: Relevance
“…In the present study, we investigated bacterial community dynamics at phylum level in degraded grasslands. Previous studies have reported that different soil bacterial phyla display different responses in abundance in grasslands following shifts in nutrient conditions (Zeng et al, 2015;Dong, Shi, et al, 2021).…”
Section: Different Phyla Taxa Showed Varied Responses To Grassland Degradationmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, we investigated bacterial community dynamics at phylum level in degraded grasslands. Previous studies have reported that different soil bacterial phyla display different responses in abundance in grasslands following shifts in nutrient conditions (Zeng et al, 2015;Dong, Shi, et al, 2021).…”
Section: Different Phyla Taxa Showed Varied Responses To Grassland Degradationmentioning
confidence: 99%
“…Previous studies that have investigated the influence of soil nutrient loss on soil microbial community structure under grassland degradation have concluded that soil nutrients regulate microbial biomass, diversity, and community composition in grasslands (Hu et al, 2014;Dong, Shi, et al, 2021); however, it is not clear how microbial community assembly in turn respond to grassland degradation. Some studies have suggested that the reason for the microbial community dynamics in degraded grasslands are associated with different responses of different phyla to soil nutrient loss and decrease in available substrate (Delgado-Baquerizo et al, 2016; Dong, Shi, et al, 2021); furthermore, biotic interactions such as facilitation, niche complementation, and competition, as major drivers of community assembly (Dong et al, 2019), influence the responses of microbial communities to modulate resource-use efficiency (Yu, Polz, et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, soil pH has strong effects on microorganisms, determining soil biological activity and imposing selection pressure on certain bacterial taxa, thereby regulating community composition (Fan et al, 2018; B. Ren et al, 2018; Zhalnina et al, 2015). Previous studies have highlighted the roles of environmental factors in regulating microbial biomass, diversity, and soil microbial community structure in grassland ecosystem (C. Dong, Shi, et al, 2021; Y. Hu et al, 2014; Widdig et al, 2020); however, it is not clear how microbial community assembly specifically responds to grassland degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Ren et al, 2018;Zhalnina et al, 2015). Previous studies have highlighted the roles of environmental factors in regulating microbial biomass, diversity, and soil microbial community structure in grassland ecosystem (C. Dong, Shi, et al, 2021;Y. Hu et al, 2014;Widdig et al, 2020); however, it is not clear how microbial community assembly specifically responds to grassland degradation.…”
mentioning
confidence: 99%